Law Enforcement towards Money Laundering Prepertrators Reviewed From the Presumption of Innocence - Rezza Ardiansyah; Eddy Rifa’i; Nikmah Rosidah (Faculty of Law, Universitas Lampung, 2021)
Law enforcement against perpetrators of money laundering crimes has recently become a separate polemic for many law enforcers who have problems, especially about the confiscation of assets suspected of being the result of money laundering, not guided by the presumption of innocence. This writing problem is how law enforcement is against money laundering perpetrators based on the presumption of innocence and how law enforcers should confiscate assets resulting from money laundering based on the presumption of innocence. Penelitian ini menggunakan pendekatan Yuridis Normatif dan Empiris. Normative research is carried out on theoretical matters in legal principles, while the empirical approach is carried out to study the law that occurs in the field. The results showed that law enforcement against money laundering perpetrators who have money laundering proceeds based on the presumption of innocence is carried out by law enforcement through confiscation. The confiscation process does not violate the principle of presumption of innocence because this is a security measure so that the suspected items do not move and transfer to a third party until the trial process is completed and has permanent legal force. Law enforcers should take action in confiscating the assets of money laundering proceeds based on the presumption of innocence must be proportional and prioritize the principles of prudence and prudence as long as it does not violate human rights and is carried out objectively by looking at whether the assets have anything to do with money laundering.